1991
DOI: 10.1177/002076409103700305
|View full text |Cite
|
Sign up to set email alerts
|

Psychotropic Drug Prescribing to Chronic Schizophrenics in a Hong Kong Hospital

Abstract: There is little information on the prescription practice for chronic schizophrenics, especially in Asia. A survey in a mental hospital in Hong Kong revealed a high mean daily dose of antipsychotics and a high frequency of use of anticholinergic drugs. The significance of these findings is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 14 publications
3
15
2
1
Order By: Relevance
“…The commonly agreed cut‐offs are 600 mg or 1000 mg CPZeq (Alvarez and Ayas, ; Sim et al ., ). Because of the age‐related changes in renal excretion and hepatic metabolism in the older patients and the fact that Asian patients require lower doses of antipsychotics and that they are more sensitive to EPS than their Western counterparts (Chiu et al ., ; Frackiewicz et al ., ), the lower cut‐off of ≥600 mg CPZeq for high dose was chosen for this study. The Schizophrenia Patient Outcomes Research Team Psychopharmacological Treatment Recommendation suggested 300–1000 mg/day CPZeq for acute and 300–600 mg/day for maintenance treatment (Ayas et al ., ).…”
Section: Discussioncontrasting
confidence: 99%
“…The commonly agreed cut‐offs are 600 mg or 1000 mg CPZeq (Alvarez and Ayas, ; Sim et al ., ). Because of the age‐related changes in renal excretion and hepatic metabolism in the older patients and the fact that Asian patients require lower doses of antipsychotics and that they are more sensitive to EPS than their Western counterparts (Chiu et al ., ; Frackiewicz et al ., ), the lower cut‐off of ≥600 mg CPZeq for high dose was chosen for this study. The Schizophrenia Patient Outcomes Research Team Psychopharmacological Treatment Recommendation suggested 300–1000 mg/day CPZeq for acute and 300–600 mg/day for maintenance treatment (Ayas et al ., ).…”
Section: Discussioncontrasting
confidence: 99%
“…Similarly, no difference in the relapse rate and in the outcome of treatment with neuroleptics was revealed in long-term studies with various neuroleptics in doses between the equivalent of 100 and 2500 mg of chlorpromazine, or at doses above versus below 310 mg day-1 [10]. The average cumulative daily doses of neuroleptics, expressed in equivalent doses of chlorpromazine, observed in this study, are similar to those reported in the treatment of schizophrenics by some authors [3,6] and half of those, reported by others [8,9]. Thus, the dosing of neuroleptics in all study locations was in the lower range, according to the available literature.…”
Section: Drug Treatment Preferences Ofschizophreniasupporting
confidence: 89%
“…18,36,37,48,50,52,56,7173,7795 In addition, treatment with quetiapine, 20,38,50,68,73,96–98 depot antipsychotics, 99101 and first-generation antipsychotics (FGAs) 68,78,85,102 has also been consistently associated with APP. Conversely, results regarding treatment with clozapine and olanzapine have been mixed.…”
Section: Resultsmentioning
confidence: 99%